CLINICAL SUCCESS OF GLASS IONOMER CEMENT REINFORCED WITH ZINC OXIDE NANO PARTICLES: A SYSTEMATIC REVIEW (CAHIERS MAGELLANES-NS, 2024)
The inclusion of zinc oxide nanoparticles (ZnO-NPs) to GIC has been considered as a development in restorative dentistry which alleviates certain drawbacks of conventional GIC. This SR effectively compares the clinical effectiveness of ZnO-NPs reinforced GIC by reviewing 28 research articles published in the last ten years. Conventional GICs are appreciated for their fluoride releasing ability, chemical bonding to tooth structures and biocompatibility; they however demonstrated low tensile strength, poor wear resistance, and sensitivity to moisture at the polymerization stage. By integrating ZnO-NPs, it is expected that these physical properties will be improved, and in addition, it will exhibit antibacterial properties on SM which is a major causative organism of secondary caries. Analyzing the effect of ZnO-NPs on the mechanical properties of GIC, the review confirms that enhance the compressive and flexural strength of GIC and therefore it is more suitable for use in high stress area of the mouth. The antibacterial properties of ZnO-NPs also help to decrease the bacterium adherence which in turn may decrease the overall rate of second caries. From clinical studies that are scarce, it has been proved that ZnO-NPs added to the GIC exhibits enhanced durability and lesser restoration failures than the regular GIC. However, there are limitations such as inability to have nanoparticle uniformly distributed within the GIC matrix and whether the composite material will cause any form of cytotoxicity in the long run. On the basis of this review, it can be inferred that ZnO NPs reinforced GIC is efficacious in restorative dentistry, nevertheless, these evidence need to be supported by subsequent clinical trials to implement the perfection in clinical protocol.